Dual‐band superconducting bandpass filter with embedded resonator structure. Issue 17 (1st August 2013) - Heng, Yong; Guo, Xubo; Cao, Bisong; Ying, Zhijun; Wei, Bin; Zhang, Xiaoping; Zhang, Guoyong; Song, Xiaoke; Wang, Jingchen
Abstract : A dual‐band superconducting microstrip filter with two passbands of 2.985–3.015 GHz and 3.045–3.075 GHz, respectively, is synthesised by a frequency transformation method. Open‐loop resonators with embedded single spiral resonators are proposed to realise the synthesised resonator frequencies and coupling coefficients. This structure has the advantages of compact size and weak parasitic couplings, which benefit the implementation of the dual‐band planar filter. The filter is successfully designed and fabricated on an MgO substrate. The measured results show high performance and match well with the simulations.